Distribution of radioactive and stable cesium in soils and plants of forest ecosystems - Seglin, Veronika; Shamal, Natalia; Kurilenko, Roman; Korol, Raisa; Dvornik, Aleksander; Nikitin, Aleksander; Simonchyk, Yuliya; Тимохина, Natallia (Journal of the Belarusian State University. Ecology, 2023)
The paper presents the results of determining the content of radioactive (137Cs) and stable (133Cs) isotopes of cesium in soil and plant samples (lichens, mosses, bark, wood) collected in a medium-aged pine forest on the territory of the Polesye State Radiation-Ecological Reserve, as well as the results of the experiment to assess the vertical precipitation of 137Cs on horizontal plates. The ratios of concentrations of 137Cs to 133Cs have been calculated, which can be used to quantify the level of equilibrium between 137Cs and 133Cs in the forest ecosystems. Based on the assumption that the physicochemical properties of 133Cs and 137Cs are similar, the analysis of 133Cs and comparison of its ratios with 137Cs can be useful for understanding the long-term behavior of the radionuclide and its equilibrium distribution in forest ecosystems. As a result of the conducted research, it was established that the precipitation activity of 137Cs in the composition of tree litter is higher in comparison with the atmospheric precipitation of the radionuclide on horizontal plates. In the autumn season, there is a decrease in the average daily values of 137Cs activity observed in the samples of radioactive fallout from the atmosphere and an increase in the tree litter samples. At the same time, more than half of the total activity of the radionuclide is retained by the tree litter. The vertical distribution of the 137Cs exchange form in the forest soil’s mineral layers was compared to that of 133Cs. The total content of 137Cs in the soil profile decreases with depth. The content of the 137Cs exchange form in the soil profile has an uneven distribution, and the concentration of the stable isotope’s exchange form increases with depth. The 137Cs to 133Cs ratios in the soil profile decrease with a soil depth from the horizon of 0–5 cm to the horizon of 15–20 cm, which indicates a nonequilibrium ratio of these isotopes. It is shown that the content of 137Cs and 133Cs in lichens, mosses, bark and wood varies depending on the type of a sample and the part of a plant. The highest activity values of 137Cs were determined in lichens and mosses. Under conditions of co-growth, mosses are characterized by a higher concentration of 133Cs when compared to lichens. A good correlation was noted between the content of 137Cs and 133Cs for all types of the plant samples. This result suggests the conclusion that these plants absorb 137Cs similarly to 133Cs.
Keywords: soil; lichen; moss; pine forest; radioactive cesium; stable cesium; isotopic ratio